Racial Disparities in Total Joint Arthroplasty Bundled Payment Data - Kaitlyn Rodriguez, MD, MS; Bruno Valan, BS; Sara Holleran, MPH; Thorsten Seyler, MD, PhD; Malcolm DeBaun, MD; Christian Pean, MD, MS (Arthroplasty Today, 2025)
Background: Bundled payment models gained traction in recent years in total joint arthroplasty (TJA) as an alternative to fee-for-service models, aiming to reduce health-care spending by holding providers accountable for quality and costs. While they can enhance care, they may inadvertently exacerbate racial health-care disparities. This study assessed racial disparities in high-cost outlier patients enrolled in the TJA bundled payment model. Methods: A retrospective review included patients enrolled in a Medicare bundled payment plan for TJA from January 1, 2022, to June 30, 2023. High-cost outliers had total adjusted costs 5% or higher than the practice mean. Statistical analysis included Wilcoxon rank sum and Chi-square tests. Results: One hundred seventy patients met the inclusion criteria: 74 underwent total hip arthroplasty and 96 underwent total knee arthroplasty. Of these, 34 identified as Black or African American, 133 as White, 2 as Other, and 1 as American Indian. The median adjusted cost for TJA for Black patients was $16,680 vs $15,720 for White non-Hispanic patients (P = .4). Black race was significantly associated with an increased emergency department return or hospital readmission (P = .013). Conclusions: Race was not associated with high-cost outliers but was linked to higher emergency department return and readmission rates. No significant difference in total adjusted cost was found between Black and White patients, though costs trended higher in the Black patients. Highlighting racial disparities in bundled payment models can help health-care stakeholders strive toward equity. Further research with larger populations is necessary to examine whether these models widen racial disparities in TJA.